ANEW RECORD OF Gunda ochracea Walker (LEPIDOPTERA: BOMBYCIDAE) FROM GUNUNG HALIMUN-SALAK NATIONAL PARK [Rekaman Baru Gunda ochracea Walker (Lepidoptera: Bombycidae) dari Taman Nasional Gunung Halimun-Salak, Jawa Barat] - Hari Sutrisno (BERITA BIOLOGI, 2008)
Gunda ochracea Walker (Lepidoptera: Bombycidae) in this report, has been recorded for the first time from Gunung Halimun-Salak National Park.So far,only G.javanica Moore is known to distribute in Java.A brief description and life pictures of a male and a female of Gunda ochracea are presented.